Comparison of consumed portion sizes and on-pack serving sizes of UK energy dense foods. (1st March 2019) - Rippin, Holly L.; Hutchinson, Jayne; Jewell, Jo; Breda, Joao J.; Cade, Janet E.
Abstract: Studies indicate a 'portion size effect' association between increased portion size and energy intake, but direct links with obesity remain unproven. UK portion size guidance is outdated and evidence suggests that on-pack serving-sizes have increased in some energy-dense foods. Serving-sizes are compared with consumed portion sizes in popular energy, fat and sugar-dense foods, and patterns explored. Data was analysed for adults aged 19-64y (excluding under-reporters) from the UK National Diet & Nutrition Survey 2008–2014 (n = 2377) for consumed portion sizes and a commercial product database of major UK retailers provided serving-sizes. Popular energy-dense food groups were split into 45 product-based subgroups. Means of consumed portion size and on-pack serving-size were calculated and compared and nutrition per 100 g and per serve was explored. Just 57% products had serving-size compared to 97% with pack-size information. Serving-size ranges were wide and varied across food groups. Consumed portion sizes were significantly higher than on-pack serving-size in all main food groups and most subgroups. The greatest difference between consumed portion size and on-pack serving-size was Crisps (44%), and within this, 'popcorn' (151%). In Chocolate and Crisps, food subgroups with the largest on-pack serving-sizes were also the most macronutrient dense. Serving-size was unavailable for many products. However, where available, consumed portion sizes were higher than on-pack serving-size in all main food groups and most subgroups. The results could inform updated portion size guidance of energy-dense foods. Further work is needed to clarify whether smaller serving and pack sizes lead to lower total consumption and energy/nutrient intake.